Beyond the Bottom Line: The Role of Personal Characteristics in Healthcare Entrepreneurship - Eliza Ciobanu; Oana Bărbulescu (Administrative Sciences)
This study fills a crucial gap by offering fresh insights into healthcare entrepreneurs’ characteristics and decision-making, enriching the understanding of entrepreneurial behavior. Employing a mixed-methods approach, by combining qualitative and quantitative data, the researchers examined how factors such as age, gender, education, number of children, marital status, and house ownership influence business orientation. Utilizing both quantitative data, collected through surveys, and statistical analyses, conducted in EViews 12, data drawn from 113 Romanian medical start-ups revealed that marital status was a significant determinant, with single individuals exhibiting a profit-centric approach, while couples or married entrepreneurs prioritize patient well-being. Also, the lower the sense of ownership, the lower the number of co-founders there was in the start-up. The motivation of entrepreneurs involved in start-ups with more than two co-founders, is based on the motivation behind a problem that directly affected the entrepreneurs themselves. An unexpected result was found regarding the healthcare entrepreneurs that perceive failure more due to lack of funding than competition, especially in profit-focused ventures, shaping their decision-making. To shape managerial implications, the authors depicted the swim lane decision-making process diagram based on these insights.